2023
DOI: 10.1111/1749-4877.12756
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation and host sex affect bat–bat fly interaction networks in the Amazonian savannahs

Abstract: Bats are the second‐most diverse group of mammals in the world, and bat flies are their main parasites. However, significant knowledge gaps remain regarding these antagonistic interactions, especially since diverse factors such as seasonality and host sex can affect their network structures. Here, we explore the influence of such factors by comparing species richness and composition of bat flies on host bats, as well as specialization and modularity of bat–bat fly interaction networks between seasons and adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Mejia et al. (2024) provided data on the interactions between bats and bat flies in one of the largest portions of the Brazilian Amazonian savannah. Here, they demonstrate that environmental variations and host sex can influence the structure of interaction networks formed between bats and their ectoparasitic flies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mejia et al. (2024) provided data on the interactions between bats and bat flies in one of the largest portions of the Brazilian Amazonian savannah. Here, they demonstrate that environmental variations and host sex can influence the structure of interaction networks formed between bats and their ectoparasitic flies.…”
mentioning
confidence: 99%
“…Mayadunnage et al (2024) mapped sightings of bare-nosed wombats with sarcoptic mange and identified environmental and spatiotemporal patterns in mange occurrence from the Wom-SAT records. Mejia et al (2024) provided data on the interactions between bats and bat flies in one of the largest portions of the Brazilian Amazonian savannah. Here, they demonstrate that environmental variations and host sex can influence the structure of interaction networks formed between bats and their ectoparasitic flies.…”
mentioning
confidence: 99%